2007
DOI: 10.1892/07-051.1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hypertriglyceridemia in Healthy Miniature Schnauzers

Abstract: Background: Idiopathic hypertriglyceridemia has been reported in Miniature Schnauzers (MS). However, studies investigating the prevalence of this disorder in a large population of MS are lacking.Hypothesis: Hypertriglyceridemia is prevalent in healthy MS. Animals: This study used 192 healthy MS and 38 healthy dogs of other breeds (control dogs). Methods: Serum triglyceride and cholesterol concentrations were measured and statistically compared in both the MS and control group. Dogs were categorized based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…It is of interest that when serum cholesterol concentrations, which have been reported to be high in 90% of all dogs with hyperadrenocorticism, 26 were measured in the 40 Miniature Schnauzers in the present study with hypertriglyceridemia, only 9 (23%) were found to have high serum cholesterol concentrations. 4 Thus, it seems unlikely that underlying hyperadrenocorticism played a role in the high serum ALP activities among Miniature Schnauzers with hypertriglyceridemia in the present study. In addition, dogs were not receiving any medications known to affect serum liver enzyme activities.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…It is of interest that when serum cholesterol concentrations, which have been reported to be high in 90% of all dogs with hyperadrenocorticism, 26 were measured in the 40 Miniature Schnauzers in the present study with hypertriglyceridemia, only 9 (23%) were found to have high serum cholesterol concentrations. 4 Thus, it seems unlikely that underlying hyperadrenocorticism played a role in the high serum ALP activities among Miniature Schnauzers with hypertriglyceridemia in the present study. In addition, dogs were not receiving any medications known to affect serum liver enzyme activities.…”
Section: Discussionmentioning
confidence: 57%
“…P ersistent hypertriglyceridemia is reportedly common in healthy Miniature Schnauzers in the United States, [1][2][3][4] with hypertriglyceridemia identified in 63 of 192 (32.8%) healthy Miniature Schnauzers in 1 study. 4 Hypertriglyceridemia in Miniature Schnauzers is characterized by an abnormal accumulation of VLDL or a combination of VLDL and chylomicrons, with or without hypercholesterolemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperlipidemic dogs, and more specifically in the hypertriglyceridemia group had a significantly increased ALP which could be related to an underlying endocrinopathy, or because of primary hypertriglyceridemia as seen in previous studies. 29 , 30 , 31 , 32 Hypertriglyceridemia has been associated with hepatocellular accumulation of triglycerides and glycogen leading to intrahepatic cholestasis and is likely of little clinical consequence. Intrahepatic cholestasis may be the underlying reason for the significant difference seen in cholestatic enzymes between hyperlipidemic and control dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs do not naturally show atherosclerosis and cholesterol-and SF-rich diets combined with thyroid suppression is required for atherosclerosis development [126]. Beagles and miniature Schnauzer dogs show useful similarities with human in cholesterol synthesis, and lipoproteins level [127,128]. Feline DM, in both spontaneous and inducible forms, therefore provides a reliable animal model of human T2D and may provide additional insights into the clinical, physiological, and pathological features of this disease (see review [129]).…”
Section: Spontaneous Animal Models Of Lipoprotein Disordersmentioning
confidence: 99%